Effectiveness of Parental Competencies and Developmental Stimulation Program by Playing on the Knowledge, Parental Child-Care, and Adaptive Behavior of Children with Autism - ศิริอำพันธ์กุล พนิดา (Journal of The Royal Thai Army Nurses, 2019)
This quasi-experimental study sought to examine the effectiveness of the parental competencies and developmental stimulation program by playing, on knowledge, parental behavior and adaptive behavior of children with autism. The autistic children (2-5 years) were randomly assigned to either the experimental or the control group. The parent and autistic children, who met the inclusion criteria and consented/assented to take part in the study, included 16 autistic children/parent dyads in the experimental group and 16 student/ parent dyads in the control group. Instruments for data collection included: An Autistic Child Care Knowledge Questionnaires, Autism Parental Behavior Questionnaires, and Vineland Adaptive Behavior Scales. Descriptive statistics, dependent t-test, independent t-test, and mean difference were used to test the effectiveness of the parental competencies and developmental stimulation program. The results demonstrated the positive effects of this program on parental behavior and adaptive behavior of children with autism. The results indicated statistical significance in mean difference scores of the Autism parental behavior and Autism adaptive behavior only (respectively, t = 4.76, p<.001; t = 2.67, p<.001). Moreover, findings presented enhancing of parental competencies and child positive adaptation and decrease in perceived caregiver burden in caring for their children with Autism. The program can help them understood children with autism, playing and learn to play with children. Playing should be applied for Autism developmental stimulation. Recommendations for further research include a larger sample size and a longer period for outcome measurements.